Physical therapists demonstrate clinical behaviors consistent with established clinical practice guidelines in managing individuals following amputation. (30th May 2022) - Bernal Salcedo, Jeremy; Treacy, Daniel; Noblet, Tim; Scrivener, Katharine
Abstract: Background and Purpose: Investigating physical therapy in amputation management offers insights into clinical practice. This study explores the self‐reported clinical practice of physical therapists in amputation management and compares it to established clinical practice guidelines to determine whether physical therapists are delivering care that is considered recommended clinical practice. Method: An online survey of Australian physical therapists with limited or extensive experience in managing individuals following amputation. Results: A total of 110 responses were received. The majority of Australian physical therapists (83%) reported their skills were adequate however, reported a lack of professional development opportunities. Physical therapists reported coordinating care with other health and medical professionals across all phases of care. They report providing comprehensive care in the following areas: residual limb management, pain management, falls prevention, education, counselling, psychological and peer support, and discharge planning. The majority of physical therapists were not aware if a comprehensive care plan was in place following a transition of care from a previous health service. Discussion: Overall, physical therapists displayed clinical practice meeting the guidelines across most areas of amputation management. Future research into alternate data collection of clinical practice, and the development of physical therapy‐specific clinical practice guidelines is needed.